Links between microbial processing of organic matter and the thermohaline and productivity features of a temperate river-influenced Mediterranean coastal area. (15th November 2019) - Celussi, Mauro; Zoccarato, Luca; Bernardi Aubry, Fabrizio; Bastianini, Mauro; Casotti, Raffaella; Balestra, Cecilia; Giani, Michele; Del Negro, Paola
Abstract: Regions of freshwater influence are affected by a constant interplay of different environmental factors that rule their seasonal and interannual highly variable dynamics. Riverine freshwater discharges alter the buoyancy of the local water masses, generating dynamic fronts and increasing water column stratification and nutrient availability. In such a heterogeneous context the paradigms for biological-physical interactions driving biogeochemical dynamics in the open seas do not always apply. We present here data from 12 surveys spanning 12 years (from 2004 to 2016) in the Po River prodelta area, which is highly representative of the above-described complexity, as it conveys the second largest freshwater discharge to the Mediterranean Sea. In particular, we focused on the microbially-mediated organic matter processing by estimating the numerical abundances of non-pigmented ('heterotrophic') and photoautotrophic ( Synechococcus ) prokaryotes, heterotrophic production and the activity of the exoenzymes beta-glucosidase, alkaline phosphatase and leucine aminopeptidase. The abundance of Synechococcus and heterotrophic prokaryotes as well as microbial activities were positively correlated to temperature and chlorophyll a concentration. Concomitantly, each variable was negatively correlated to salinity. In high-temperature, high salinity and low chlorophyll a samples, the heterotrophic production was limited and deviated from the typical linearity of the Arrhenius' law, suggesting resource limitation rather than temperature control. A multivariate analysis performed to analyze the pattern of organic matter degradation/utilization highlighted 11 distinct clusters of functional diversity. Temperature, salinity and chlorophyll a concentration data alone were able to explain most of the functional cluster separation as evidenced by a regression tree analysis. For freshwater-influenced samples, salinity was the only variable affecting metabolic patterns, whereas in typically marine waters, at salinity ≥37, metabolic profiles were determined by specific combinations of all 3 parameters. Highlights: 309 samples from 12 surveys were analyzed in a river-influenced area. Seasonality and river inputs determined large gradients in organic matter processing. 11 different clusters of functional diversity were detected. Temperature, salinity and chlorophyll a data explained most of the functional diversity.